PERILAKU PENGGEREKAN DAN PERKEMBANGBIAKAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK RAMIN - P Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The tunneling and breeding habits of ambrosia beetle Platypus trepanatus Chapman (Coleoptera: Platypodidae) were studied in the field for 26 days after initial burrowing.The tunneling is initiated by the male beetle, commenced hours after the ramin tree (Gonystylus bancanus Kurz.) is felled. As the beetle tunnel about twice its body length, the burrowing is stopped, and the beetle, then, remains inside near the entrance hole to entice the female beetle for joining.After arriving, the female beetle takes over the tunneling extension. The male, on the other hand, occupies the initial tunnel, builds a circular fibrous plait ringed at the entrance hole, and cleans the tunnel by ejecting frass outside. An established tunnel is determined by the ejection of coarse frass first and the fine other then. A successful tunneling (broods) seems to be attributable to the parent beetles care.The beetle tends to burrow the log across the grain. The first tunneling is radially, but by the day about 12, it has significantly curved. The speed of tunneling is approximately 4.47 mm while the depth of its penetration is about 2.56 mm per day.The oviposition is firstly recorded between the day 2-8 at the length of tunnel 9-25 mm. The egg stadium is about two weeks. No pupation was shown during these 26 day studies.Statistical computations reflect that the tunneling and oviposition were still continued after these observations